Irrigation variability and climate change affect derived distributions of simulated water recharge and nitrate leaching. Issue 6 (18th August 2018) - Green, Timothy R.; Anapalli, Saseendran S.
ABSTRACT: Irrigation ('blue') water has high value as municipalities seek water security under growing populations and projected climates, but spatial variability makes estimating return flows to groundwater challenging. We demonstrate a framework for simulating spatially variable infiltration and derived distributions of return flows using an agricultural and vadose zone model to simulate recharge and nitrate leaching under irrigated corn in semi-arid northeastern Colorado, USA. Derived distributions indicated increased historical recharge (2–42%) as the spatial variability of applied irrigation increased. Projected climate in 2050 increased recharge above historical rates by up to 58%, but climatic effects decreased with increasing irrigation variability.